Optimizing the Home Industry Business Model through the Business Model Canvas for the 'Queen of Laundry' Business in Surabaya: Implementation of the 2025 Ministry of Education and Culture Technology Grant Program (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This study aims to optimize the business model of the Ratunya Laundry Surabaya home industry through the Business Model Canvas (BMC) approach, specifically in the context of changes before and after the technology grant in the form of large-capacity dryers and washing machines. The method used is a case study with a qualitative descriptive approach, involving direct observation, interviews with business owners, and documentation of operational activities. The BMC analysis was conducted by mapping nine main elements, including customer segments, value propositions, distribution channels, customer relationships, revenue streams, key resources, key activities, key partners, and cost structures. The results show that after the technology grant, production capacity increased from an average of 40 kg/day to 120 kg/day, service time decreased from 2–3 days to 6–8 hours for regular services, and even 3 hours for express services. In addition, the customer segment expanded from the local scope to include small hotels, guesthouses, and other commercial customers. The financial impact was also significant with an average revenue increase of 40–60% within six months. This study concludes that the implementation of BMC is effective as an analysis and strategic planning tool for home industries, especially when integrated with appropriate technological support. The results of this study can serve as a reference for other micro-business actors in identifying opportunities for growth and sustainable business model innovation.